LINGUISTIC ERRORS OF USING INDONESIAN IN FOREIGN LEARNERS’ WRITINGS - Ni Wayan Sri Darmayani; Ketut Artawa; Made Sri Satyawati (Universitas Warmadewa, 2018)
This research was aimed at describing errors of using Indonesian in foreign learners’ writings and understanding causing factors of those errors. This research applied qualitative-descriptive approach method. The data were sixteen Indonesian writings written by foreign learners. The findings of this study reveal that there are such linguistic errors related to spelling, such as: errors in capitalization, error in writing affixed and root words, error in writing numbers, error in using punctuations, and error in writing borrowed word; related to morphology, such as: error in using the root, error in morphophonemic process, and error in using affixes; related to syntax, such as: errors in phrase structure and errors in sentence structure; and related to lexicon, such as: the use of pleonastic words, errors in word choice, and the use of unnecessary interrogative words. Moreover, the causing factors of those errors are linguistic and non-linguistic factors. Linguistic factors can be classified into three factors, they are interlingual factor, intralingual factor, and the daily use of Indonesian. Meanwhile, non-linguistic factors can be classified into two factors, they are imperfect language learning and learner’s community environment.